2020
DOI: 10.1155/2020/1017979
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for a Career in Dentistry among Dental Students and Dental Interns in Kenya

Abstract: A number of factors have been cited as determinants for choosing a career in dentistry around the globe. The purpose of this study was to determine motivations for a career in dentistry among dental students and dental interns in Kenya. This was a cross-sectional study where 293 individuals participated by filling and returning self-administered questionnaires. The mean age of all respondents was 22.3 years. Overall, 59.5% of the respondents had selected dentistry as their preferred career at the end of high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
6
11
2
Order By: Relevance
“…While this could be a reflection of the privileged social background of our participants, it is heartening to see that humane considerations are important for both medical and dental students, as studies show that altruism protects from burnout 8 . Our results are consistent with those from Kenya which showed 74% dental students motivated by the idea of serving people, and from Islamabad which showed that while 13% were motivated by the idea of service to humanity, only 6.3% were attracted by monetary gain 17,18 . In contrast, a study in Saudi Arabia showed both medical (87.5%) and dental (80%) students motivated by financial independence, with more dental students (75%) compared to medical (65%) attracted by the prospect of making a lot of money 6 .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…While this could be a reflection of the privileged social background of our participants, it is heartening to see that humane considerations are important for both medical and dental students, as studies show that altruism protects from burnout 8 . Our results are consistent with those from Kenya which showed 74% dental students motivated by the idea of serving people, and from Islamabad which showed that while 13% were motivated by the idea of service to humanity, only 6.3% were attracted by monetary gain 17,18 . In contrast, a study in Saudi Arabia showed both medical (87.5%) and dental (80%) students motivated by financial independence, with more dental students (75%) compared to medical (65%) attracted by the prospect of making a lot of money 6 .…”
Section: Resultssupporting
confidence: 91%
“…A study of >4000 medical students in Latin America showed being male associated with significantly higher level of social/altruistic motivations than for females 20 . A study from Kenya which showed 74% male and female dental interns motivated by the opportunity to care for people showed no significant difference between the two groups 17 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This study indicates that the motives for studying dentistry among entry-level students in Libya were related to the nature of dentistry as a profession, including working in the healthcare field, scientific knowledge, and realizing that there were different specialties in dentistry. These findings are consistent with previous studies conducted in African countries that showed the altruistic nature of motives to study dentistry [ 17 , 18 ]. However, variations in the motives to study dentistry in different societies and countries are well-documented [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Personal preference, the main reason for postgraduate path selection in this study, was similar to Baharvand et al (Baharvand, Moghaddam, Pouretemad, & Alavi, 2011) findings in Iranian dental students and Lukandu (Lukandu, Koskei, & Dimba, 2020) on Kenyan dental students. Personal preference as the main reason for choosing a speciality field is quite encouraging since it will lead to many enthusiastic postgraduate students and future specialists in that particular field.…”
Section: Discussionsupporting
confidence: 89%